2017
DOI: 10.1123/jsr.2017-0035
|View full text |Cite
|
Sign up to set email alerts
|

Stroboscopic Vision to Induce Sensory Reweighting During Postural Control

Abstract: Context: Patients with somatosensory deficits have been found to rely more on visual feedback for postural control. However, current balance tests may be limited in identifying increased visual dependence (sensory reweighting to the visual system), as options are typically limited to eyes open or closed conditions with no progressions between. Objective: To assess the capability of stroboscopic glasses to induce sensory reweighting of visual input during single-leg balance. Design:Descriptive Setting: Laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 11 publications
2
31
1
Order By: Relevance
“…Specifically, if higher level visual-sensory integration of spatial information supporting motor cortex efficiency is a key neuroplastic factor driving the success of training, then modifications to the training can be made to target these neural processes. Potential clinical examples include optimization of exercise progression not only on classic muscle or motor performance but considering visual–spatial or sensory challenges to add difficulty, this could include stroboscopic training, 19 dual tasking, perturbation training, or even isolated neurocognitive training to improve visual–spatial abilities. Additionally, the use of neural stimulation techniques combined with feedback modality differentiation and precision (eg, dosage specifications, adding auditory or tactile feedback to increase sensory region activity) may have future application as well as new yet to be imagined interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, if higher level visual-sensory integration of spatial information supporting motor cortex efficiency is a key neuroplastic factor driving the success of training, then modifications to the training can be made to target these neural processes. Potential clinical examples include optimization of exercise progression not only on classic muscle or motor performance but considering visual–spatial or sensory challenges to add difficulty, this could include stroboscopic training, 19 dual tasking, perturbation training, or even isolated neurocognitive training to improve visual–spatial abilities. Additionally, the use of neural stimulation techniques combined with feedback modality differentiation and precision (eg, dosage specifications, adding auditory or tactile feedback to increase sensory region activity) may have future application as well as new yet to be imagined interventions.…”
Section: Discussionmentioning
confidence: 99%
“…36 Typically, visual perturbation training has been limited to eyes open and eyes closed conditions with no progression between, but SG provides the ability to incrementally perturb visual information by increasing the duration of the opaque state (range: 25 to 900 msec) relative to the constant duration of the transparent state (100 msec). 88 Originally designed to be a mobile sports training tool, SG has allowed researchers to investigate the effects of perturbed vision in context-specific environments. 89 Early research with SG explored behavioral performance on motion coherence, divided attention, multiple-object tracking, 90 short-term visual memory, 91 and anticipation, 92 as well as performance on sports-specific tasks from singleleg squatting, 93 ice hockey, 94 tennis, 95 and badminton.…”
Section: Sensory Reweighting Therapy Visual Perturbation Trainingmentioning
confidence: 99%
“…Therefore, including a specific treatment option that focuses on this neurophysiologic dysfunction would be beneficial for these patients. Kim et al [ 18 ] have reported the influence of stroboscopic vision (SV) to induce sensory reweighting of visual input in CAI patients. Stroboscopic vision consisted of the use of a special goggle whose glasses intermittently turn from transparent to opaque for 100 milliseconds and thus reduced the visual feedback.…”
Section: Introductionmentioning
confidence: 99%